Penerapan Model Pembelajaran ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction): Sebuah Model Pembelajaran Untuk Meningkatkan Kemampuan Pemahaman Konsep Siswa - manik, alda sephia; Yayan Carlian; Inne Marthyane Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low conceptual understanding ability of students, which is seen in low student learning outcomes. This low conceptual understanding is thought to be due to learning that tends to be teacher-centered and does not involve students actively. The purpose of this study was to determine the difference in the improvement of conceptual understanding ability of students who follow learning by applying the ARIAS model and the direct instruction model. This study used a quantitative approach with a quasi-experimental method with a non-equivalent control group design. The research sample consisted of 26 students of class VI-A as the experimental class and 26 students of class VI-C as the control class. Data collection techniques were in the form of tests and observations. The data analysis technique used an independent t-test with a significance level of 5% with the hypothesis of a difference in the average increase in students' conceptual understanding ability between those using the ARIAS model and those using the direct instruction model. The results showed that students' conceptual understanding ability after applying the ARIAS model increased by 0.62 with a moderate category. Students' conceptual understanding ability after using the direct instruction model increased by 0.46 with a moderate category. There was a difference in the average increase between the two classes as evidenced by the independent t-test. The results showed a significance value of 0.001. This means that 0.001 <0.05, the hypothesis is accepted, indicating a difference in the average improvement in conceptual understanding between those using the ARIAS model and the direct instruction model.